Entrepreneurship Processes and Small Farms Achievements: Empirical Analysis of Linkage - Temidayo Gabriel Apata (Journal of Entrepreneurship, Management and Innovation)

(untitled)
Entrepreneurship process has been argued as opportunity-driven, creative, and resource-efficient, that could influence income generation of small farmers that adopted entrepreneurial skills and innovation into their farming operations. This study examines entrepreneurship process strategies employed to income increase by small farmers, evidence from southwest of Nigeria. The sampling procedures entail three stages of samples selection of 240 farmers but only 200 data was useful. Descriptive statistical and inferential statistics were used to analyze and describe the data. Respondents’ age ranges from 16 to 65 years old, mean age was 36.16 years. The study found out that 5 % of the samples had modest communication skills that aid adoption of effective entrepreneurial processes and about 83% have a strong belief in one’s self to succeed. Successful farmers had multiple sources of related income generation business ventures. Targeting the entrepreneurs for support could make them even more effective.